“Womanspace”, Geobodies and Borderlands - Biljana Kašić ([sic])
It is time to radically rethink the question of the political – is how contemporary theorist Enrique Dussel explained the motive to write his Twenty (20) Theses on Politics [20 Tesis de política], almost six years ago. In one of his theses he stated that the radical transmutation of the political system is actually a “response to new interventions by the oppressed and excluded” (Dussel 112), or in other words, that it relies on other spaces and impulses of the political, namely on those which are dedicated to engaging in critical, that is, liberating actions. A year ago, in a joint public conversation between two leading feminist theorists – Judith Butler and Gayatri Chakravorty Spivak – organized by the Centre for Postcolonial Theory in Frankfurt in May 2011 and devoted to critique today, the main meaning of critique was expressed neither as a method nor as a theoretical position, rather as its potency to explore “how it may be possible to think”; namely, the way “in which we pose the question of the limits of our most sure ways of knowing, doing and thinking” (Judith Butler & Gayatri Chakravorty Spivak 2011) is what constitutes a sense of critique, what makes it workable.